1998
DOI: 10.1080/02688699844952
|View full text |Cite
|
Sign up to set email alerts
|

Dural osteochondroma: case report, review of the literature and proposal of a new classification

Abstract: Complete excision of a dural osteochondroma is presented. Upon reviewing the literature we noted that basal and convexity osteochondromas, although considered as a single pathological entity, differ in epidemiology, pathogenesis, management and natural history. A new classification is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Total surgical removal is considered to be the only effective treatment for osteochondroma, 3,[12][13][14][15]19,21,26) but the present tumor adhered tightly to the pituitary stalk, making total removal impossible. We found that partial removal relieved the compression of the optic chiasm and nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total surgical removal is considered to be the only effective treatment for osteochondroma, 3,[12][13][14][15]19,21,26) but the present tumor adhered tightly to the pituitary stalk, making total removal impossible. We found that partial removal relieved the compression of the optic chiasm and nerve.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][28][29][30][31]33) Intracranial osteochondromas are rare, accounting for less than 1% of all intracranial space-occupying lesions, 4,12) and can arise from the skull base, convexity, and other intracranial regions. [2][3][4]6,[12][13][14][15][19][20][21][22]25,26,[28][29][30][31] The vast majority of intracranial osteochondromas occur at the base of the skull and can be categorized into three groups: sellar turcica osteochondroma, parasellar osteochondroma, and clival osteochondroma. [2][3][4]14,15,20,22,26,28,30) Here we describe an unusual case of sellar turcica osteochondroma mimicking hemorrhagic pituitary adenoma.…”
Section: Introductionmentioning
confidence: 99%
“…Osteocartilaginous tumors are exceedingly rare, are usually dural‐based, develop in the skull and only secondarily displace dura and brain . To our knowledge, extraosseous osteoma, chondroma, osteochondroma, mesenchymal chondrosarcoma, osteosarcoma and aneurysmal bone cyst have been seldom described in the CNS. A few cases of unusual dura‐based periosteal osteoblastoma have also been reported in cranial bones, such as temporal bone and frontal cranial bone .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 21 English-language articles documenting calcified lesions of the sellar region, published from 1961 to 2015, were retrieved from the database. 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Pathologies included cerebral aneurysm, 16 chondroid chordoma, 20 chondroma, 13 craniopharyngiomas, 19,22 OCs, [6][7][8][9][10][11] odontome, 18 osteoma, 17 pituitary adenomas, 15,21 pituitary stone, 25 Rathke cleft cyst, 23 retinoblastoma, 14 schwannoma, 24 and xanthogranuloma. 12 Among them, six patients were documented as OC cases.…”
Section: Demographic Datamentioning
confidence: 99%
“…3 It arises infrequently in the cranial cavity, presenting as calcified foci and accounts for < 1% of all intracranial space-occupying lesions. 4 Most OCs originating from the skull base are from the middle fossa, where the cranial sutures converge. Hence OCs are thought to arise from the cartilaginous rests in the basilar synchondroses.…”
Section: Introductionmentioning
confidence: 99%